Prosthodontic Management of Segmental Mandibulectomy Patient with Guidance Appliance and Overlay Denture - Aruna, U. (Springer India, 2012)
Patients who undergo segmental or hemi-mandibulectomy suffer from various postoperative problems in esthetics and function. The solution to such problem is providing a mandibular guidance appliance to correct mandibular deviation to resected side due to loss of muscle action on the affected side. This article describes the treatment of a female patient who underwent segmental mandibulectomy on right side secondary to adenoid cystic carcinoma of the base of tongue. An acrylic guidance appliance was constructed to help control the mandibular deviation and co-ordinate masticatory movements. The prosthesis was worn continuously by the patient for 1 month which corrected the occlusion on the left side. To compensate for the open-bite caused due to rotation of mandible following partial mandibulectomy, an overlay removable partial denture was given. The patient was satisfied with the improvement in esthetics and mastication.